Die "Evangeliese Sending" 2010 - uitgedien of relevant? - P. Robinson (Acta Theologica)
The Evangelical Mission (EM) dates its official history back to 1846 with the establishment of the Evangelical Alliance with as common goal ‘to promote unity and fellowship among Christians for more effective witness to the gospel’ and ‘to foster interpersonal relationships of common faith, trust and prayer’. This they achieved by several general mission conferences: Liverpool 1860, London 1888, and New York 1900. Several youth organisations, like SVM and YMCA and some Churches received membership. Nevertheless the EA was always less keen on their structural expression of unity. The movement invested high hopes on the International Mission Conference at Edinburgh 1910 to accelerate its goal of world evangelisation. Several factors lead to dissatisfaction with the outcomes and later developments regarding church-based mission. Eventually the EA group withdrew from the churches’ ecumenical movement. A process of re-grouping and re-defining of its identity followed, leading to the watershed Lausanne Conference 1974 and its subsequent structures and projects. The movement presents itself energetically to the 21st century in Cape Town during its Edinburgh 2010 Conference.